Effect of differing amounts of microalgae (Schizochytrium limacinum) added via milk on performance and antioxidant capacity of dairy calves (Research, Society and Development, 2020)
This study evaluated the effect of different amounts of marine microalgae (Schizochytrium limacinum) via milk on performance, serum constituents and antioxidant indicators of dairy calves. Twenty-four Holstein calves were distributed to one of four treatments (six replicates) according to a completely randomized design: a control treatment (without microalgae), or microalgae supplementation at 6, 12 and 18 grams of microalgae per day supplied via milk. Two blood samples were taken, at 21 and 42 days of the experiment, to measure activities of antioxidant enzymes: glutathione S-transferase (GST), catalase (CAT), superoxide dismutase (SOD) as well as levels of reactive oxygen species (ROS). The supplementation of increased amount of microalgae did not influence dry matter intake (DMI) and performance (P>0.05). At the 21 days of life, there was a linear increase in serum protein (P = 0.03), globulin (P = 0.006) and in SOD activity (P = 0.05). Linear reduction in ROS (P = 0.001) and a quadratic effect for heavy immunoglobulin G (IgG) (P = 0.02) were observed as the microalgae amounts increased. Close to weaning, at 42 days, serum globulin (P = 0.003), GST (P = 0.002) and SOD (P = 0.02) linearly increased with the inclusion of microalgae. Conversely, enzymatic activity of CAT showed a quadratic effect (P = 0.05). Supplementation of microalgae via milk did not influence intake and performance dairy calves. However, the use of microalgae as a feed additive to dairy calves at amount of 6 g/d is recommended due to its stimulation of antioxidant enzymes and reduction on serum levels of free radicals.